2023
DOI: 10.1021/acs.analchem.3c03294
|View full text |Cite
|
Sign up to set email alerts
|

A Photoreactor-Interfaced Mass Spectrometer: An Online Platform to Monitor Photochemical Reactions

Oisin J. Shiels,
Maria Menti-Platten,
Fostino R. B. Bokosi
et al.

Abstract: An experimental platform is reported that allows for the online characterization of photochemical reactions by coupling a continuous flow photoreactor, equipped with LED light irradiation and a dual-tipped ESI source, directly to a mass spectrometer with electrospray ionization. The capabilities of this platform are demonstrated with two classes of photoreactions: (1) the photopolymerization of methyl methacrylate and (2) photocatalyzed alkyne insertion into a 1,2,3-benzotriazinone. The online technique provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…To examine the denitrogenation step in more detail, online mass spectrometry experiments using a quartz reaction cell were performed to allow monitoring of intermediate and product formation (see Supporting Information for more details, including Figures S3 and S4). Initial experiments demonstrated that photoactivation of [Ir­(ppy) 2 (dtbbpy)]­PF 6 in the presence of DIPEA promotes N 2 loss from 1,2,3-benzotriazin-4­(3 H )-one 1a ( m / z 269 [M •+ + MeOH]) to generate the reactive intermediate 11a ( m / z 210 [M – + H + ] •+ , Figure a). Note that for the neutral species 1a , formation of the radical cation occurs during electrospray ionization (ESI), followed by noncovalent coordination with methanol (producing [M •+ + MeOH], whereas for the radical anion 11a , protonation and radical cation formation during ESI produces [M – + H + ] •+ (see Figure S5 for the anion detected in negative mode).…”
Section: Resultssupporting
confidence: 90%
“…To examine the denitrogenation step in more detail, online mass spectrometry experiments using a quartz reaction cell were performed to allow monitoring of intermediate and product formation (see Supporting Information for more details, including Figures S3 and S4). Initial experiments demonstrated that photoactivation of [Ir­(ppy) 2 (dtbbpy)]­PF 6 in the presence of DIPEA promotes N 2 loss from 1,2,3-benzotriazin-4­(3 H )-one 1a ( m / z 269 [M •+ + MeOH]) to generate the reactive intermediate 11a ( m / z 210 [M – + H + ] •+ , Figure a). Note that for the neutral species 1a , formation of the radical cation occurs during electrospray ionization (ESI), followed by noncovalent coordination with methanol (producing [M •+ + MeOH], whereas for the radical anion 11a , protonation and radical cation formation during ESI produces [M – + H + ] •+ (see Figure S5 for the anion detected in negative mode).…”
Section: Resultssupporting
confidence: 90%